A vision for arts led urban renewal in Adelaide and the City West Campus of the University of South Australia - Garnaut, Christine (International Planning History Society Proceedings, 2018)
Various perspectives on universities and urban renewal in the post-industrial era are considered in the international literature. These include universities’ roles as drivers of physical environmental change and of economic and social improvement; their relationships, and sometimes tensions, with immediate and wider neighbours; and the social, infrastructure, economic, cultural, educational, and local environmental sustainability benefits of a university’s presence for a city and its residents. One theme within the literature on universities’ economic and cultural contributions is their potential and actual role in the evolution and development of arts and cultural quarters. This paper considers that topic in relation to the University of South Australia’s City West campus that opened in 1997 in an area of Adelaide known as the West End. The campus was built adjacent to an emerging arts complex. Soon after UniSA announced its decision to move to the new location, the Adelaide City Council commissioned the West End Urban Development Strategy to optimise the benefits of the university’s presence. This paper introduces and reviews that Strategy and a subsequent, related, initiative of the City Council and the South Australian Government to establish the West End as an arts and cultural quarter.